Hubungan Kepemimpinan dan Gaji Dengan Kepuasan Kerja Perawat Pelaksana di Ruang Rawat Inap Rsud Pariaman - Hilma Yessi; Rika Armalini; Mike Asmaria; Kheniva Diah Anggita; Hasmita Hasmita (Jurnal Ners, 2025)
Nurses' dissatisfaction with hospital policies and administration can lead to serious consequences for the hospital, as nearly 80% of care is provided by nurses. The aim of this study is to analyze the factors related to job satisfaction among nurses in the inpatient wards of RSUD Pariaman. This is a descriptive correlational study with a cross-sectional design, using a questionnaire for data collection. Data analysis was conducted using univariate, bivariate, and multivariate analysis. There was no relationship between nurses' characteristics and promotion opportunities with job satisfaction. However, leadership, the nature of the job, salary, and feedback were found to have a relationship with job satisfaction. The most dominant factor influencing job satisfaction is feedback. Recommendations for the hospital management to enhance job satisfaction include paying more attention to feedback: responding to suggestions made by nurses, monitoring job development, providing positive encouragement, and evaluating nurses' performance.